Mechanistic Studies on the Organocatalytic α‐Chlorination of Aldehydes: The Role and Nature of Off‐Cycle Intermediates. (3rd August 2018) - Ponath, Sebastian; Menger, Martina; Grothues, Lydia; Weber, Manuela; Lentz, Dieter; Strohmann, Carsten; Christmann, Mathias
Abstract: Herein we report the isolation and characterization of aminal intermediates in the organocatalytic α‐chlorination of aldehydes. These species are stable covalent ternary adducts of the substrate, the catalyst and the chlorinating reagent. NMR‐assisted kinetic studies and isotopic labeling experiments with the isolated intermediate did not support its involvement in downstream stereoselective processes as proposed by Blackmond. By tuning the reactivity of the chlorinating reagent, we were able to suppress the accumulation of rate‐limiting off‐cycle intermediates. As a result, an efficient and highly enantioselective catalytic system with a broad functional group tolerance was developed.